All-organic composites of ferro- and piezoelectric phosphonium salts for mechanical energy harvesting application - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry of Materials, 2019)
Molecular ferroelectrics owing to their lightweight, flexibility, and phase stability are drawing attention in the fields of flexible electronics, optical devices, and energy materials. In this paper, we report a series of binary organoamino phosphonium salts containing triphenyl isopropylaminophosphonium (TPAP), diphenyl diisopropylaminophosphonium (DPDP), phenyl triisopropylaminophosphonium (PTAP), and tetraisopropylaminophosphonium (TIAP) cations supported by lower symmetric tetrahedral BF4-, ClO4-, and IO4- anions. The P-E hysteresis loop measurements on these polar organic salts gave high remnant polarization (P-r) values of 35.36, 21.83, and 21.12 mu C cm(-2) for the DPDP center dot BF4, DPDP center dot ClO4, and DPDP center dot IO4 salts, respectively, having 1D hydrogen-bonded chain structures built from strong N-H center dot center dot center dot X (X = F or 0) interactions. For the first time, highly flexible composite devices have been prepared for the piezoelectric salts TPAP center dot BF4, DPDP center dot BF4, and TIAR center dot BF4 using thermoplastic polyurethane (TPU) as the matrix. The observed maximum peak-to-peak output voltages (V-pp) for the 10 wt % composite devices of TPAP center dot BF4/TPU, DPDP center dot BF4/TPU, and TIAP center dot BF4/TPU are found to be 7.37, 8.95, and 4.75 V, respectively. These composite devices exhibit excellent durability, cycling stability, and viscoelastic properties. They also show the capacitor charging capabilities reaching their maximum charging points within 60 s.